2015
DOI: 10.21608/jppp.2015.75787
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION, INSECTICIDAL EFFECT AND ANTIBIOSIS STUDIES OF SOME BACTERIA ISOLATED FROM NATURALLY INFECTED Pectinophora gossypiella (SAUND.) COLLECTED FROM COTTON FIELDS IN EGYPT.

Abstract: One of the important Integrated Pest Management Strategies (IPM) against economic pests in Egypt is the use of biological control methods.The use of entomopathogenic bacteria is one of these methods. The authors achieved four isolates of bacteria from the naturally infected P. gossypiella in cotton fields at Assuit and Kafr El-Sheikh Governorates, Egypt. Isolates were characterized based on morphological properties. Morphological analyses were carried out based on Bergey's Manual of Systematic Bacteriology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…kurstaki exhibited its effect against S. exigua and Helicoverpa armigera (Zhang et al, 2009), Plutella xylostella (Legwaila et al, 2015). Abou-zeid et al (2015) revealed that Staphyloccus sciuri and Micrococcus luteus were the most effective against 1 st instar larvae of P. gossypiella. Many studies have reported the susceptibilities of lepidopteran larvae to Bt toxins (Alsaedi et al, 2017;Hanen et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…kurstaki exhibited its effect against S. exigua and Helicoverpa armigera (Zhang et al, 2009), Plutella xylostella (Legwaila et al, 2015). Abou-zeid et al (2015) revealed that Staphyloccus sciuri and Micrococcus luteus were the most effective against 1 st instar larvae of P. gossypiella. Many studies have reported the susceptibilities of lepidopteran larvae to Bt toxins (Alsaedi et al, 2017;Hanen et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The tested biocide Btk (Dipel 2×) caused different influences on all biological aspects of pink bollworm which decreasing larval duration, pupation percentage and adult emergence (Hegab and zaki 2012). Furthermore, their latent effect caused the lowest pupation % resulted from treated P. gossypiella larvae by Staphyloccus sciuri and Micrococcus luteus (Abou-zeid et al, 2015). The percentages of pupation and adult emergence of P. gossypiella were negatively correlated with the increase of spore-crystal concentration and positively with the increase in the concentration of the supernatant of B. cereus (Mahfouz and Abou El-Ela 2011).…”
Section: Discussionmentioning
confidence: 99%